TECHNOLOGY OF GEOSPATIAL DATA ACQUISITION USING PHOTOGRAMMETRIC METHODS FOR GIS - IVANOV, DENYS; SERGIEIEVA, KATERYNA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article examines the main technological aspects of applying photogrammetric methods for the acquisition, processing, and editing of spatial datasets employed in contemporary cartographic practices and geographic information systems (GIS). Special attention is paid to the development of analytical and digital photogrammetry as key tools for spatial modeling of the real world. The main areas of research include: 1) improvement of analytical photogrammetric methods for the acquisition and vectorization of topographic information using analytical stereoplotters, which ensure high accuracy in interpreting spatial coordinates based on stereoscopic observation of aerial photographs; 2) investigation of the efficiency of using next-generation digital photogrammetric systems, including highly calibrated photogrammetric scanners, digital workstations, and specialized software (such as tools for automatic orthorectification, digital stereoscopic visualization, phototriangulation, and the generation of digital elevation models (DEM)), which enable integration with remote sensing (RS) data; 3) optimization of processes for editing and managing topographic information using modern GIS platforms, which allow for high productivity in the creation of geospatial data bases for various levels of topographic support. The article also analyzes the evolution of photogrammetric technologies in the context of automation of digital aerospace image processing in central and panoramic projections, which serve as a basis for high-precision cartographic products and provide informational support for spatial planning, natural resource monitoring, infrastructure management, environmental monitoring, and scientific research. The significance of geospatial data in the development of the National Spatial Data Infrastructure (NSDI) is highlighted, as it serves as a key element in the digital transformation of spatial management systems and the creation of prerequisites for ensuring sustainable territorial development.